1989
DOI: 10.1172/jci114062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MB creatine kinase isoform conversion in vitro and in vivo in dogs.

Abstract: Time-dependent removal of the COOH-terminal lysine residue from each subunit of tissue MM creatine kinase by plasma carboxypeptidase N produces two additional isoforms that are readily separated, thereby permitting sensitive, early detection of acute myocardial infarction. Only two isoforms of MB creatine kinase have been detected in plasma leading to speculation that the COOH-terminal lysine on the B subunit is resistant to hydrolysis. To define the biochemical changes resulting in MB creatine kinase isoform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Several studies have shown that carboxypeptidase N is the main factor accounting for isoform conversion in human plasma under physiological conditions (7)(8)(9)(10)(11) and after myocardial infarction, elucidating in particular the relation between carboxypeptidase N activity in plasma and observed rates of creatine kinase-MM isoform conversion (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that carboxypeptidase N is the main factor accounting for isoform conversion in human plasma under physiological conditions (7)(8)(9)(10)(11) and after myocardial infarction, elucidating in particular the relation between carboxypeptidase N activity in plasma and observed rates of creatine kinase-MM isoform conversion (13).…”
Section: Discussionmentioning
confidence: 99%
“…(circulating des-lysine isoform) ratio is a sensiis available for their ™asurement, this assay is also an tive and specific marker for the early diagnosis of acute mterestm S too1 for the earl y diagnosis of acute Wocardial infarction in emergency (5,6). Previous studies (1)(2)(3)(4)(5)(6)(7)(8)(9) indicated that the tissue creatine kinase-MB 2 iso-1) Enzymes:…”
mentioning
confidence: 99%
“…17 The column was equilibrated with 20 mM Tris-Cl, pH 8.4. A sample of supernatant containing 1 mg protein18 was applied to the column and eluted with a linear gradient of NaCl from 0 to 400 mM (10 mmol/ml) in 20 mM Tris-Cl, pH 8.4, containing 5 mM 2-mercaptoethanol.…”
Section: Analysis Of Enzymatic Activity Of Individual Creatine Kinasementioning
confidence: 99%
“…Especially, the existence of perhaps 3 CK-MB isoforms must be clarified. 42,43 Myoglobin: Myoglobin is a cytosolic hemoprotein in cardiac and skeletal muscles (M, 17,700) necessary for the last step in the oxygen transport to the mitochondria.71*72 Normal serum levels of myoglobin are reported to be in the range of 6-85 ng/mL and 4-60 ng/mL for men and women, respectively. 3o After acute myocardial infarction, the serum concentration of myoglobin becomes abnormal in about 2 hours, peaks in about 6-9 hours, and becomes normal in 24-36 hours.…”
Section: Role Of Cardiac Serum Proteinsmentioning
confidence: 99%